Advanced strategies for combating bacterial biofilms. Issue 9 (29th January 2019) - Sharahi, Javad Yasbolaghi; Azimi, Taher; Shariati, Aref; Safari, Hossein; Tehrani, Melika Khanzadeh; Hashemi, Ali
Abstract: Biofilms are communities of microorganisms that are formed on and attached to living or nonliving surfaces and are surrounded by an extracellular polymeric material. Biofilm formation enjoys several advantages over the pathogens in the colonization process of medical devices and patients' organs. Unlike planktonic cells, biofilms have high intrinsic resistance to antibiotics and sanitizers, and overcoming them is a significant problematic challenge in the medical and food industries. There are no approved treatments to specifically target biofilms. Thus, it is required to study and present innovative and effective methods to combat a bacterial biofilm. In this review, several strategies have been discussed for combating bacterial biofilms to improve healthcare, food safety, and industrial process. Abstract : Bacteria are the cause of evolution of several strategies to deal with problems and challenges existing under hostile environments. One of the significant survival strategies used by bacteria is a biofilm formation. we have tried to provide a comprehensive picture of current knowledge about antibiofilm agents of different sources.